A new technique for comparing solar dynamo models and observations - Mininni, P.D. (2004)
We present a new technique suitable for a detailed comparison between solar dynamo models and observations. The method is based on the technique of dynamo spectroscopy proposed by Hoyng & Schutgens (1995) and bi-orthogonal decomposition of solar data. This decomposition provides a representation of the mean and fluctuating components of the flows, yielding relevant information for the comparison. To illustrate the method, we use a simple kinematic dynamo model of the solar cycle. Irregularities are introduced in the evolution of the magnetic fields modeling the turbulent behavior of the solar convective region with a random perturbation on the external source for the poloidal field. After fine tuning the parameters of the model we obtain solar like solutions displaying a magnetic cycle of 22 years, with fluctuations in its period and amplitude. In addition, the model generates Maunder-like events with a time span of 60-100 years.